Alteration of glass surface via polyvinyl butyral (PVB) layer for reverse mode polymer dispersed liquid crystal (R-PDLC) display. (2nd September 2017) - Ahmad, Farzana; Jamil, Muhammad; Jeon, Young Jae
ABSTRACT: The purpose of this study is to optimize the optical contrast of reverse mode polymer disperse liquid crystal (R-PDLC) display by applying an extra polyvinyl butyral (PVB) layer. The resin PVB has been selected due to its characteristics for the glasses such as strong binding, optical clarity, strong adhesion, toughness and flexibility. It has been found that on coating of PVB (0.1 wt%) layer considerably enhanced the optical contrast of R-PDLC display by increasing the ON-state scattering. The basis of following behavior has been investigated by special techniques such as UV-spectroscopy, thermo-optic evaluations for variations in nematic to isotropic transition temperature ( T NI ) and contact angle measurements. Following findings have revealed a raise in contrast ratio by increasing ON-state scattering with slight alterations in OFF-state transmittance. This behavior has been considered due to increase in roughness and hydrophobicity towards LC molecules that alter the ON-state scattering.